2020
DOI: 10.1002/cam4.3135
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of neutrophil to lymphocyte ratio and platelet to lymphocyte ratio in advanced hepatocellular carcinoma patients treated with anti–PD‐1 therapy

Abstract: Background Currently, there are no recognized or validated biomarkers to identify hepatocellular carcinoma patients (HCC) likely to benefit from anti–PD‐1 therapy. We evaluated the relationship between neutrophil‐lymphocyte ratio (NLR) and platelet‐lymphocyte ratio (PLR) and survival outcomes, pretreatment and after three doses (posttreatment) of nivolumab in HCC patients. Methods Medical records of HCC patients treated with nivolumab between June 2016 and July 2018 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
96
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 27 publications
7
96
2
Order By: Relevance
“…Neutrophil-to-lymphocyte ratio with cutoff of five is one of the most frequently reported peripheral blood inflammatory factor with efficacy or prognostic value for patients receiving anti-PD-1therapy in advanced urothelial and hepatocellular carcinoma, non-small cell lung cancer, head and neck cancer and Melanoma ( Bartlett et al, 2020 ; Dharmapuri et al, 2020 ; Nassar et al, 2020 ; Peng et al, 2020 ; Ueda et al, 2020 ). Previous studies have shown that the increase of NLR value is positively correlated with the proportion of combined positive score of PD-L1 < 1 and the decrease of tumor infiltrating lymphocytes ( Franz et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophil-to-lymphocyte ratio with cutoff of five is one of the most frequently reported peripheral blood inflammatory factor with efficacy or prognostic value for patients receiving anti-PD-1therapy in advanced urothelial and hepatocellular carcinoma, non-small cell lung cancer, head and neck cancer and Melanoma ( Bartlett et al, 2020 ; Dharmapuri et al, 2020 ; Nassar et al, 2020 ; Peng et al, 2020 ; Ueda et al, 2020 ). Previous studies have shown that the increase of NLR value is positively correlated with the proportion of combined positive score of PD-L1 < 1 and the decrease of tumor infiltrating lymphocytes ( Franz et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Platelets induce epithelial-to-mesenchymal migration of circulating tumor cells and promote tumor cell extravasation and metastasis ( Schumacher et al, 2013 ; Copija et al, 2020 ). It is reported high NLR and PLR are associated with poor outcome and are useful predictors of the efficacy of anti–PD-1 therapy in many cancers ( Dharmapuri et al, 2020 ; Kartolo et al, 2020 ). In this study, we found that PLR only was the factor influencing PFS in univariate analysis for patients treated with anti-PD-1 therapy in GC and CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Several biomarkers have been reported for patient selection with melanoma or non-small cell lung cancer; however, all were not effective in HCC patients. For HCC patients, a 10% reduction of serum alpha-fetoprotein level at 4 weeks or lower serum NLR and PLR at 6 weeks after treatment were mentioned as a marker of patient selection with disease control [ 32 , 33 ]. However, these were post-treatment markers and could not be used to predict tumor response prior to treatment for patient selection.…”
Section: Discussionmentioning
confidence: 99%
“…Although a large literature already exists on the use of various common blood tests that reflect systemic inflammation and prognosis, and to a lesser extent reflecting in turn the extent of the disease [ [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] ], the precise relationship of inflammatory markers to tumor extent has not been well defined. The current work attempts to do this by use of the commonly used PLR and NLR ratios, to assess their relationship to MTD and to try to find their ability to predict small tumor size (MTD).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation-based prognostic scores have been shown to be associated with survival [ 3 ] and with various parameters of tumor aggressiveness [ 4 ]. This may be related to the involvement in tumor growth of a variety of easily measurable indices of inflammation [ 5 ] in routine clinical blood tests, including levels of neutrophils, lymphocytes, monocytes, platelets, albumin, C-reactive protein (CRP), as well as marker ratios, such as albumin and CRP (Glasgow Index), neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) and monocyte-to-lymphocyte ratios, amongst others [ [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] ]. In the current study, NLR and PLR were evaluated with reference to maximum tumor diameter (MTD) and also to survival in a large Turkish HCC cohort.…”
Section: Introductionmentioning
confidence: 99%